Ethnic Group and Mother Tongue in the Ethiopian Censuses of 1994 and 2007 - Hudson, Grover (Aethiopica, 2012)
Results for ethnic groups and mother tongues of the 1994 and 2007 Ethiopian census are presented and compared. There are ethnic groups without mother tongues and mother tongues without ethnic groups. Names of ethnic groups and mother tongues differ in the two censuses, and only some of the differences are explained as synonymous names. Some of the differences remain unexplained, and some of the names are unidentified. In one case, Səlṭi, the census seems to have attributed its speakers to another, unrecognized group. The census reports 38 % total Ethiopian population growth from 1994 to 2007, and comparable increase is generally apparent for all but a few groups listed. Some groups with small populations in 1994 do not reappear 2007.